Epistemic bubbles and echo chambers in the progress of science - Albuquerque, Ulysses (Ethnobiology and Conservation, 2025)
Does epistemic diversity necessarily promote scientific progress, or does this idea persist more as a normative principle than as an empirical finding? In this hypothesis-essay, I argue that scientific pluralism does not automatically entail epistemic fluidity. Distinct scientific communities may share publication venues and rhetorical commitments while remaining epistemically insulated. Building on recent debates about epistemic bubbles and echo chambers, I suggest that even within science, traditionally conceived as a self-correcting enterprise, mechanisms of selective exposure and institutional filtering can restrict genuine epistemic permeability. Frequently presented as an inherently diverse discipline, ethnobiology offers a revealing context for exploring whether declared plurality translates into dialogical openness or stabilizes into parallelism. The argument does not treat ethnobiology as a confirmed case, but as a field in which this hypothesis of pluralism without fluidity can be examined. I invite a reconsideration of how epistemic contact, reflexivity, and institutional design shape the moral and cognitive architecture of scientific progress.